2006
DOI: 10.1007/s10342-006-0112-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of defoliation caused by the sawfly Cephalcia lariciphila (Hymenoptera: Pamphilidae) on radial growth of larch (Larix decidua Mill.)

Abstract: The period between 2000 and 2002 repeated outbreaks of the web spinning sawfly Cephalcia lariciphila (WACHTL 1898) around the village of Veˇtrny´Jenı´kov, Czech Republic. The impact of defoliation, caused by C. lariciphila feeding, on tree-ring formation of European larch (Larix decidua Mill.) was studied using dendrochronological methods. Heavy defoliation resulted in much less growth in the years of insect attack, the average incremental loss being 67% for the 2000-2002 period. Also, defoliation resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…However, as winter moth defoliates Quercus while the leaves are expanding, and since latewood growth is proportionally dependent upon actively produced photosynthate from within the current year, the photosynthetic capabilities of the defoliated tree may be reduced and/or photosynthate may be allocated to processes (e.g., defense, re-leafing) other than latewood growth. This relationship between defoliation in the current year and latewood growth has been demonstrated with other defoliators [ 26 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 69%
“…However, as winter moth defoliates Quercus while the leaves are expanding, and since latewood growth is proportionally dependent upon actively produced photosynthate from within the current year, the photosynthetic capabilities of the defoliated tree may be reduced and/or photosynthate may be allocated to processes (e.g., defense, re-leafing) other than latewood growth. This relationship between defoliation in the current year and latewood growth has been demonstrated with other defoliators [ 26 , 45 , 46 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 69%
“…Forests of almost any composition of species worldwide can be affected by insect infestations and subsequent dieback, leading to devastating results (e.g. Vejpustková & Holuša 2006; Carus 2009). The impact of insect herbivory looms as a significant threat to the health of large areas of forest worldwide, as habitats are placed under ever increasing levels of anthropogenic stress (Crawley 1989).…”
Section: Introductionmentioning
confidence: 99%
“…and European larch (Larix decidua Mill.) that had been defoliated by the European web-spinning larch sawfly (Cephalcia lariciphila Wachtl) (Filion and Cournoyer, 1995;Vejpustkova and Holusa, 2006). In years, when insect defoliation depletes the tree's resources to an extreme level, the tree may form no annual ring or may only form xylem cells incompletely around the circumference of the cambium.…”
Section: Discussionmentioning
confidence: 99%
“…Given eastern hemlock's late successional status and its responsiveness to climate, most eastern hemlock tree-ring studies have focused on reconstructing stand dynamics or reconstructing climate-growth relationships (Abrams et al, 2000;Hart et al, 2010); however, the introduction of HWA provides an unusual opportunity to study the decline and mortality of a foundation species through its tree-ring record. Previous studies on other insect-defoliated trees have shown a consistent pattern of reduced radial growth following infestation because the consumption of foliage results in a loss of stored carbohydrates and lower potential photosynthetic rates (Vejpustkova and Holusa, 2006). These reductions in growth within the host species are typically accompanied by growth increases in non-host trees as mortality of the host species increases availability of light, space, and nutrients (Alfaro et al, 1991).…”
Section: Introductionmentioning
confidence: 92%